2001
DOI: 10.1076/ceyr.22.3.215.5516
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide participates in cataract development in selenite-treated rats

Abstract: The present study demonstrated that NOS inhibitors prevented the development of cataracts in selenite-treated rats. The results also suggest that nitric oxide had an important role in the development of selenite-induced cataracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 17 publications
1
36
0
1
Order By: Relevance
“…17) We previously reported that the increase in Ca 2ϩ concentration in lenses resulted in cataract development in cataract model rats, and the induction of iNOS protein occurred prior to the elevation of Ca 2ϩ content in the lenses. [18][19][20] In addition, the administration of disulfiram, a dimer of DDC, and AG can prevent lens opacification in the Shumiya cataract rat (SCR), UPL rat, and selenite-induced cataract rat. [18][19][20] Nitric oxide (NO) is synthesized from the guanidino-nitrogen of L-arginine and molecular oxygen by NOS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17) We previously reported that the increase in Ca 2ϩ concentration in lenses resulted in cataract development in cataract model rats, and the induction of iNOS protein occurred prior to the elevation of Ca 2ϩ content in the lenses. [18][19][20] In addition, the administration of disulfiram, a dimer of DDC, and AG can prevent lens opacification in the Shumiya cataract rat (SCR), UPL rat, and selenite-induced cataract rat. [18][19][20] Nitric oxide (NO) is synthesized from the guanidino-nitrogen of L-arginine and molecular oxygen by NOS.…”
mentioning
confidence: 99%
“…[18][19][20] In addition, the administration of disulfiram, a dimer of DDC, and AG can prevent lens opacification in the Shumiya cataract rat (SCR), UPL rat, and selenite-induced cataract rat. [18][19][20] Nitric oxide (NO) is synthesized from the guanidino-nitrogen of L-arginine and molecular oxygen by NOS. iNOS, one of the three isoforms of NOS, 21) is usually not present under normal conditions, is Ca 2ϩ independent, and induced by cytokines, such as interferon-gamma (IFN-g) and tumor necrosis factor a (TNF-a).…”
mentioning
confidence: 99%
“…Selenite causes increasing lipid peroxidation and oxidation of sulfhydryl groups and damage of membranes of lens fibres. This mechanism resembles age-related cataract [23]. These processes lead to protein aggregation and result in a decrease the water soluble proteins followed by opacification of the lens [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium deficiency has been shown to cause increased oxidative stress and trigger cataractogenesis by increasing inducible NO synthase (iNOS) expression and NO release. Pretreatment of rats with NO synthase inhibitors has been shown to prevent onset of selenite-induced cataract and reduce lens calcium content [95]. Culture of human lens epithelial cells in magnesium deficient medium shows 6 fold increase in expression of İNOS as compared to those cultured in medium with normal magnesium concentration.…”
Section: Magnesium: Have a Role In Cataractogenesis?mentioning
confidence: 99%